Evaluation of the Safety of the Way Sekampung Bridge Against Extreme Flooding for the 50 Year Return Period - Al Rasyid, Burhan Najib; Purwadi, Ofik Taufik; Tugiono, Subuh; Zakaria, Ahmad (Jurnal Teknik Sipil dan Lingkungan, 2025)
The purpose of this study is to evaluate the Sekampung Way Bridge, which is located on the Sumatra Cross Road on the border between Bumi Agung Village in Tegineneng District, Pesawaran and Mandah Village in Natar District, South Lampung, with coordinates 105°10'33.75"T 5°11'49.65"S, is in the process of being rebuilt to improve services to road users. In conducting a bridge planning study, river hydrological factors must be analyzed to take into account the flood level and vertical clearance, so that the bridge remains safe despite extreme flooding. According to the Highway regulations, permanent bridges are generally planned with a building life of 50 years, For rivers that do not carry drift, the minimum clearance value is 1.0 meter. Therefore, the hydrological analysis was carried out using the Nakayasu HSS method with a Q50 discharge of 426.96 m³/second in 2.7 hours. From the results of 1D and 2D hydraulic analysis using HEC-RAS version 6.4.1, it shows that the elevation of the flood water level with a 50-year re-period is at an elevation of +75.23 m to +75.38 m, while the base elevation of the Way Sekampung Bridge is at an elevation of +79.44 m. Therefore, the clearance of the Way Sekampung Bridge is 4.21 m to 4.06 m, so it can be concluded that this bridge is safe from flood risk with a 50-year re-enactment period, although the potential for flooding around the Way Sekampung river bridge area is large. This is due to the slope of the river around the location of approximately 2.5%.